The Effect of PORPE (Predict, Organize, Rehearse, Practice and Evaluate) Strategy towards Reading Comprehension - Efa Silfia (Journal of English Education Studies, 2018)
Reading comprehension is the message that is imposed in the written form. It is most important element that students must recognize, because the primary purpose of reading comprehension is to know the way in getting what the students want to know from reading material. In fact, most of the students got difficulties to understand reading text because they think that answering reading is not interesting task and not explicitly stated on the text. The aim of this research is to find out whether any significant effect of using PORPE toward reading comprehension. The research used experimental method. The population was students at Eleventh grade in SMAN 3 Kota Jambi. The sample was divided into two randomized group: XI IPA 1 as experiment class and XI IPA 2 as control class. The instrument of the research had been done in reading comprehension test. The data of the research showed that after counting the students’ scores and analyzing by using t-test formula, the result of experimental class was significantly higher than the students’ score in control class. It was showed at the level of significance 0.05 with the degree of freedom (df) 60, t-observed value 2.512 > t-table value 2.000. The null hypothesis (Ho) was rejected and alternative hypothesis (H1) was accepted. The conclusion was using PORPE strategy affected the students’ reading comprehension.